Effect of prophylactic clipping in colorectal endoscopic resection: A meta‐analysis of randomized controlled studies. Issue 6 (1st October 2017) - Nishizawa, Toshihiro; Suzuki, Hidekazu; Goto, Osamu; Ogata, Haruhiko; Kanai, Takanori; Yahagi, Naohisa
Abstract : Background and aim: The efficacy of clipping for preventing delayed bleeding after colorectal endoscopic resection is still controversial. To assess the efficacy of prophylactic clipping, we conducted a meta‐analysis of randomized controlled trials. Methods: We searched PubMed, the Cochrane library, and the Igaku‐chuo‐zasshi database for randomized trials eligible for inclusion in our meta‐analysis. We identified seven eligible randomized trials from the database search, and compared the effect of clipping versus non‐clipping with respect to delayed bleeding and perforation. Data from eligible studies were combined to calculate pooled odds ratios (ORs). Results: Postoperative bleeding was observed in 41 of 1526 cases (2.7%) without clipping and in 32 of 1533 cases (2.1%) with clipping (OR 0.76, 95% CI: 0.39–1.47, p  = 0.414). There was no significant heterogeneity among the trial results (I‐Square = 26.7%, p  = 0.22). In the subgroup analysis based on small tumor size (<20 mm) and large tumor size (≥20 mm), there were no significant differences. Compared with non‐clipping, the pooled OR of developing perforation with clipping was 1.00 (95% CI: 0.14–7.25), indicating no significant difference between the two groups. Conclusions: Prophylactic clipping did not decrease the occurrence of delayed bleeding after colorectal endoscopic resection. Clipping could be of interest in patients with a high risk of bleeding (anticoagulation) or large lesions, but with the available trials data to prove this are scarce.